On the Prins reaction of terminal olefins and formaldehyde in trifluoroacetic acid - Almohseni, H; Stent, M; Hodgson, D (Springer Verlag, 2018)
The Prins reaction of 1-heptene, as a representative terminal alkene, with formaldehyde in trifluoroacetic acid produces 3-butyl-4-(trifluoroacetoxy)tetrahydropyran and/or 3-butyl-4-hydroxytetrahydropyran; it does not provide (as previously reported by Talipov and coworkers) a route to 3-alkyl-2,5-dihydrofurans and 4-alkyl-3-hydroxytetrahydrofurans.